2013
DOI: 10.3390/ijms14023467
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and DNA Damage in Human Gastric Carcinoma: 8-Oxo-7'8-dihydro-2'-deoxyguanosine (8-oxo-dG) as a Possible Tumor Marker

Abstract: We characterized the oxidative stress (OS) status by the levels of reduced/oxidized glutathione (GSH/GSSG), malondialdehyde (MDA) and the mutagenic base 8-oxo-7′8-dihydro-2′-deoxyguanosine (8-oxo-dG) in human gastric carcinoma (HGC) samples and compared the results with normal tissue from the same patients. We also analyzed 8-oxo-dG in peripheral mononuclear cells (PMNC) and urine from healthy control subjects and in affected patients in the basal state and one, three, six, nine and twelve months after tumor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 70 publications
(85 reference statements)
2
57
0
1
Order By: Relevance
“…Total protein content is measured by the Lowry method [33].

8-oxo-dG assay in serum by HPLC-EC

Assay of 8-oxo-dG in serum was performed following the method by Li et al (2013) [20] with slight modification reported by Borrego el at. (2013) [26]. For 8-oxo-dG separation and quantification, a Waters 515 HPLC Pump (model n° 5200ª) with 5 µm Spherisorb ODS2 column (4.6 mm x 250 mm) and electrochemical detectors (HPLC-EC) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Total protein content is measured by the Lowry method [33].

8-oxo-dG assay in serum by HPLC-EC

Assay of 8-oxo-dG in serum was performed following the method by Li et al (2013) [20] with slight modification reported by Borrego el at. (2013) [26]. For 8-oxo-dG separation and quantification, a Waters 515 HPLC Pump (model n° 5200ª) with 5 µm Spherisorb ODS2 column (4.6 mm x 250 mm) and electrochemical detectors (HPLC-EC) was used.…”
Section: Methodsmentioning
confidence: 99%
“…6,9,11,14,15,22,34,35,37 Oxidative stress leads to oxidative DNA damage, making 8-oxoguanosine, a marker for oxidative DNA damage, an ideal candidate biomarker for detecting and assessing gastric cancer. 15,47 A defective antioxidant response Heme oxygenase 1 (HO-1), a potent antioxidant and antiinflammatory enzyme that is responsible for the degradation of heme, has well-studied and wide-ranging protective functions across many disease models. 49 HO-1 expression is induced by the presence of nitric oxide (NO), leading to decreased IL-8 expression and inflammation.…”
Section: Increased Expression Of Spermine Oxidase During H Pylori Inmentioning
confidence: 99%
“…15,47 8-oxoguanosine and 8-OHdG assays measure oxodized nucleotide adducts, which form as a result of oxidative DNA damage. 47 They are considered direct markers for DNA damage and surrogate markers for ROS production in vivo. 47 Quantitative measurement of ROS in gastric tissues in vivo is difficult, but dihydroethidine staining has been utilized for qualitative studies in infected mice.…”
Section: Increased Expression Of Spermine Oxidase During H Pylori Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Within cancer research, the use of biomarkers is an important tool for the early detection of cancer and for determining prognosis. As DNA damage is a hallmark of carcinogenesis, signatures of DNA damage, specifically 8-oxoG, may serve as powerful biomarkers for gastric cancer [5,80]. 8-oxoG and 8-OHdG assays can measure nucleotide adducts that reflect oxidative DNA damage [80] and serve as direct markers of DNA damage and proxy markers for oxidative stress in vivo [14,21,80].…”
Section: Ape-1: Enzyme That Is Responsible For Creating a Nick In Thementioning
confidence: 99%